1996
DOI: 10.1111/jon19966281
|View full text |Cite
|
Sign up to set email alerts
|

Middle Cerebral Artery Velocity Correlates with Nitroglycerin‐induced Headache Onset

Abstract: Headache often accompanies treatment with nitroglycerin, but the cerebral hemodynamic effects and the exact mechanism of the headache are incompletely understood. Transcranial Doppler monitoring allows evaluation and monitoring of changes in blood flow velocity in the large intracranial arteries. The objective of this study was to assess middle cerebral artery (MCA) blood flow velocities with transcranial Doppler monitoring in subjects receiving continuous low-dose nitroglycerin intravenously or by patch, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…There were no statistical differences in baseline velocity among the 3 groups of patients and controls. In contrast to results reported by other investigators, we found no significant changes in PI in the groups of subjects during the entire evaluation 15,16 …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…There were no statistical differences in baseline velocity among the 3 groups of patients and controls. In contrast to results reported by other investigators, we found no significant changes in PI in the groups of subjects during the entire evaluation 15,16 …”
Section: Resultscontrasting
confidence: 99%
“…In our subjects, BFV in the MCA decreased significantly in migraineurs during headache attacks caused by nitroglycerin, but did not in controls; in the treated groups with migraine, BFV increased significantly after zolmitriptan and sumatriptan administration. Our results are in agreement with the findings of other investigators 6,12,16,17 …”
Section: Commentssupporting
confidence: 94%
“…In contrast, the headache had disappeared at this time point making it unlikely that dilation per se of MCA is the cause of NO-induced headache. This is supported by findings in another study on GTN, where MCA velocities remained decreased (14%, P  < 0.001) at the time of headache resolution [31]. In addition, dilation of the MCA outlasted the headache response after intravenous dipyridamole [32] and sildenafil-induced migraine in migraine patients, but did not affect MCA velocity [33].…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, in the present study, the automated approach also gave the smallest numeric values of the MCA. Former studies have reported a correlation between the onset of pharmacologically induced headache and dilation of the MCA (33,34). We did an explorative post-hoc correlation analysis of the headache score and cross-sectional MCA area for the whole observation period.…”
Section: Present Resultsmentioning
confidence: 99%